2008
DOI: 10.2134/agronj2007.0291
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Irrigated Continuous Corn under Conventional‐Till and No‐Till in Northern Colorado

Abstract: Conversion of irrigated cropland from conventional tillage (CT) to no‐till (NT) could have several environmental benefits including reduced erosion potential, reduction of greenhouse gas emissions, and conservation of water. However NT must be economically viable if it is to be adopted. Costs of production and economic returns were evaluated for an irrigated, continuous corn (Zea mays L.) system under CT and NT over 6 yr on a clay loam soil in northern Colorado. Yield responses to N fertilization were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…At this site, the interaction of tillage and N fertilizer requirement has been well documented with CT optimizing yields at roughly 177 kg N ha −1 compared to NT optimizing yields at 239 kg N ha −1 after 9 years . Despite lower yields under NT and a higher N requirement at this site, Archer et al (2008) found the NT system provided a greater economic benefit compared to CT due to substantial reduction in tractor traffic. Stover yields increased with N fertilizer rate and are in the range of those published previously from this site from 1999 to 2009 ranging from 5.7-9.0 Mg ha −1 across all N rates (Follett et al, 2013;.…”
Section: Particulate Organic Mattermentioning
confidence: 71%
“…At this site, the interaction of tillage and N fertilizer requirement has been well documented with CT optimizing yields at roughly 177 kg N ha −1 compared to NT optimizing yields at 239 kg N ha −1 after 9 years . Despite lower yields under NT and a higher N requirement at this site, Archer et al (2008) found the NT system provided a greater economic benefit compared to CT due to substantial reduction in tractor traffic. Stover yields increased with N fertilizer rate and are in the range of those published previously from this site from 1999 to 2009 ranging from 5.7-9.0 Mg ha −1 across all N rates (Follett et al, 2013;.…”
Section: Particulate Organic Mattermentioning
confidence: 71%
“…The UAN+AgrotainPlus had lower N 2 0 emissions per megagram grain than UAN. The blank and check treatments had the lowest level of N 2 O emissions per megagram grain, but these are not economically sustainable management practices (Archer et al, 2008; Archer and Halvorson, 2010). The N 2 O emissions per megagram grain were slightly higher in 2010 than in 2009, consistent with the higher level of N 2 O emissions in 2010 than in 2009 (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrous oxide has a global warming potential (GWP) approximately 298 times greater than that of CO 2 (Solomon et al, 2007), thus the importance of developing methods to reduce N 2 O emissions in agricultural systems. Nitrogen fertilization is essential for optimizing crop yields and economic returns in irrigated cropping systems in the U.S. Central Great Plains (Archer et al, 2008; Archer and Halvorson, 2010; Maddux and Halvorson, 2008). Nitrogen fertilizer application generally increases N 2 O production from cropping systems (Bouwman et al, 2002; Hao et al, 2001; Dusenbury et al, 2008; Mosier et al, 2006, Halvorson et al, 2008, 2010a; Van Groenigen et al, 2010).…”
mentioning
confidence: 99%
“…However, reduced-and conservation tillage (Figure 1b), which minimally disturb the soil surface and crop residues, allow for the sequestration of atmospheric carbon to the OPEN ACCESS soil [2]. Reduced-and conservation tillage methods require fewer passes over the soil with farm machinery, thus saving fuel and further reducing net agricultural greenhouse gas emissions [5,6]. Residues from crops and other vegetation act as a barrier to wind and water, reducing erosion and evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown of surface residues increases soil fertility over time. Whereas conservation tillage cropping systems often have reduced yields in comparison with conventional-till systems, cost reductions in labor, equipment, fuel, and irrigation increase net farm profitability [5][6][7], particularly when coupled with conservation subsidies and the sale of carbon sequestration credits [1,2]. Tillage practice is also an important variable for biogeochemical models in agricultural soils [1,2].…”
Section: Introductionmentioning
confidence: 99%